The Analysis of Financial Literacy, Financial Attitude and Locus of Control Toward Financial Behavior on UNESA's Economic and Business Students - Alifa Salsabila Hidayat; R.A Sista Paramita (Profesional Muda Cendekia Publishing, 2022)
Financial behaviour is a concept related to a person's ability to manage (plan, budget, audit, manage, control, seek, and store) daily financial funds. Behavioural finance is a combination of financial theory and the laws of economics and psychology. The emergence of financial behaviour is the impact of the desire to meet the needs of life according to income. As an advantage, a person will tend to spend his personal finances wisely. This type of research uses quantitative methods. The population in this study were 97 respondents, using a non-probability sampling method, namely purposive sampling. Data analysis used multiple linear regression method with the help of SPSS version 24 program. The results showed that the hypothesis testing of financial literacy, financial attitude, and locus of control partially had a positive and significant effect on the financial behaviour of students of the Faculty of Economics and Business, Surabaya State University.